Parallel Laser Micro/Nano‐Processing for Functional Device Fabrication - Li, Yang; Hong, Minghui (Laser & photonics reviews, 2020)
Photolithography is one of the most commonly used techniques in semiconductor manufacturing, which is the foundation for all the modern electronic device fabrication. However, deep and extreme ultraviolet lithographic systems as well as the corresponding photomasks are both relatively expensive. The fabrication methods are based on the low‐speed high‐cost electron‐beam lithography or focused‐ion‐beam etching. Therefore, a maskless high‐speed method is highly recommended for the micro/nano‐structure fabrication. Among all these maskless methods, direct laser writing (DLW) is an important and widely adopted micro‐processing technique. Based on the nonlinear exposure, the feature size can achieve down to tens of nanometers. However, the speed of DLW is a technical bottleneck. To overcome this issue, parallel DLW methods are developed, including the self‐assembly microspheres laser patterning, laser interference lithography, and multifocal array DLW. Herein, the principles, advantages, challenges, and applications of these parallel processing technologies are summarized. Nanoscale resolution for large area arbitrary periodic pattern fabrication is achieved. Meanwhile, these technologies have the unique ability to build 3D structures instead of conventional 2D patterns, which is the direction of future micro/nano‐fabrication. These techniques are widely applied to surface processing and functional device fabrication in the field of sensing, solar cells, and metamaterials. Photolithography is the most commonly used technique in semiconductor manufacturing, which relies on photomask. The maskless method can directly fabricate the micro/nano‐structure, including the photomask. However, this faces a technical bottleneck regarding fabrication speed. Parallel laser processing methods are developed for high speed functional device fabrication, which is the direction of future micro/nano‐fabrication.